A new species of Miconia (Melastomataceae: Miconieae) from the eastern slope of the Peruvian Andes - Ocampo, Gilberto; Almeda, Frank (Phytotaxa, 2014)
Miconia glandulipetala is described as a new species from the eastern slope of the central Peruvian Andes. This new species is recognized as a member of the “Leandra + Ossaea (scorpioid)” clade based on its secund flowers and ovoid seeds with testa cells in an aligned pattern and par-convex periclinal walls. The taxon is easily recognized by the presence of 4-merous flowers, 4-locular ovaries, and a subapical glandular hair formed on the margin of each petal.